LEAF GROWTH KINETICS AND SHOOT DEVELOPMENT IN GRAFTED SELECTIONS OF MAMEY SAPOTE - Ledesma Miramontes, Alejandro; Villegas Monter, Ángel; González Hernández, Víctor Arturo; Ruiz Posadas, Lucero del Mar; Mora Aguilera, Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
The aim of this study was to evaluate the growth of vegetative organs in six selections of mamey sapote (Pouteria sapota (Jacq.) H. E. Moore & Stearn), grafted of three and four years in the soil’s and climatic conditions of Alpoyeca, Guerrero; in order to understand the behavior of trees from Alpoyeca Yucatán, Guerrero, were evaluated: kinetics of leaf growth, total growth of shoot, leaf area index, leaf unit weight and thickness of the leaf. The results showed that mamey’s leaves reach their maximum development at 42 days but, at 23 days they have 80% of their total size and can be photosynthetically self-sufficient. The total growth of buds on the 3 year old trees during one year was 62.9 to 72 cm, and the period of highest growth was from June to September, while in the 4-year old trees was of 40.7 to 44.1 cm and the period of highest growth from April to August. ‘El Regalo’ selected in Alpoyeca, Guerrero, presented the highest values of leaf area index, specific leaf weight and thickness of the leaf, while ‘Dany 66’ from Yucatán had the lowest. The specific weight of the leaf is a variable that changes with the phenology of the plant, which should be evaluated at least three stages to get reliable results.
Keywords: Pouteria sapota; leaf area index; leaf thickness; Sapotaceae; specific leaf weight